Aqueous extract of Inocutis levis improves insulin resistance and glucose tolerance in high sucrose-fed Wistar rats - Zahra Ehsanifard; Fereshteh Mir-Mohammadrezaei; Alireza Safarzadeh; Masoomeh Ghobad-Nejhad (Shahrekord University of Medical Sciences, 2017)
Introduction: Inocutis levis is a polypore fungus belonging to Hymenochaetales of basidiomycetes. The specie is mainly distributed in Asia and grows on living angiosperm trees. This study investigates the effect of aqueous extract of I. levis on insulin resistance and glucose tolerance in high sucrose fed (HSF) rats. Methods: Male rats were given 30% sucrose solution for 12 weeks. The extract of I. levis at doses of 50 and 150 mg/kg body weight was intraperitoneally administered for 2 weeks in HSF rats. Blood glucose, serum insulin, insulin resistance index (HOMA-IR) and histological changes of pancreas were evaluated. Results: Sucrose solution significantly increased the insulin, glucose and HOMA-IR levels, compared to the control. At the dose of 50 mg/kg the extract decreased glucose and insulin, and improved insulin resistance relative to that of HSF rats which did not take the extract. Histological studies on pancreas tissue indicated no significant difference in the size of Langerhans islets of HSF rats and HSF rats treated with the extract at dose of 50 mg/kg compared to the control group. But, treatment with the dose of 150 mg/kg of I. levis increased islets diameter and number of cells in the islets of Langerhans in HSF group. Conclusion: Inocutis levis extract may have hypoglycemic effects, by regulating insulin secretion and improving glucose tolerance, and seems to be able to ameliorate pancreatic islets in HSF rats. Our findings indicate that I. levis can be considered as a potential treatment with medicinal properties to alleviate insulin resistance and to prevent risk of type 2 diabetes in a dose dependent manner.